(untitled) (Research, Society and Development, 2022)
Objective: To compare the pedobarographic findings of plantar pressure distribution in individuals with typical diabetic neuropathy with non-diabetic individuals. Methods: 25 patients with typical diabetic neuropathy were randomly selected and another 25 non-diabetic patients were selected electively. After undergoing clinical examination according to the report and recommendations of the San Antonio Conference on Diabetic Neuropathy, glycated hemoglobin (HbA1c) and static podobarography tests were performed to identify pressure points in the feet and distribution of plantar pressure. Results: The mean age of 62.24 (± 9.01) years, mean body mass index (BMI) of 29.69 (± 5.9) Kg / m² and mean HbA1c of 8.9 (± 3.29% of non-diabetic patients, mean age was 61.04 (± 9.69). The mean hallucin pressure in the diabetic group was 111.16 (± 64.25) kPa, in the non-diabetic group was 78.91 (± 4.43) Kg / m² and HbA1c was 5.3 (± 0.24) ± 38.48) kPa and the comparison showed ap = 0.015. Conclusion: An increase in pressure was found in the hallux region of diabetic patients when compared to non-diabetic patients.